The soluble guanylate cyclase CYG12 is required for the acclimation to hypoxia and trophic regimes in Chlamydomonas reinhardtii. (28th December 2017) - Düner, Melis; Lambertz, Jan; Mügge, Carolin; Hemschemeier, Anja
Summary: Oxygenic phototrophs frequently encounter environmental conditions that result in intracellular energy crises. Growth of the unicellular green alga Chlamydomonas reinhardtii in hypoxia in the light depends on acclimatory responses of which the induction of photosynthetic cyclic electron flow is essential. The microalga cannot grow in the absence of molecular oxygen (O2 ) in the dark, although it possesses an elaborate fermentation metabolism. Not much is known about how the microalga senses and signals the lack of O2 or about its survival strategies during energy crises. Recently, nitric oxide (NO) has emerged to be required for the acclimation of C .  reinhardtii to hypoxia. In this study, we show that the soluble guanylate cyclase (sGC) CYG12, a homologue of animal NO sensors, is also involved in this response. CYG12 is an active sGC, and post‐transcriptional down‐regulation of the CYG12 gene impairs hypoxic growth and gene expression in C .  reinhardtii . However, it also results in a disturbed photosynthetic apparatus under standard growth conditions and the inability to grow heterotrophically. Transcriptome profiles indicate that the mis‐expression of CYG12 results in a perturbation of responses that, in the wild‐type, maintain the cellular energy budget. We suggest that CYG12 is required for the proper operation of the photosynthetic apparatus which, in turn, is essential for survival in hypoxia and darkness. Significance Statement: How oxygenic phototrophs deal with environmental conditions that cause intracellular energy crises is vital for ecosystems. Here we show that the soluble guanylate cyclase CYG12 of Chlamydomonas reinhardtii is involved in the acclimation to conditions that challenge the energy budget. The data suggest that CYG12 is required for the proper functioning of photosynthesis, and that the state of the photosynthetic apparatus during the day influences survival in hypoxia and during the night.